Relativistic and resonant effects in the ionization of heavy atoms by ultra-intense hard X-rays - Benedikt Rudek (Nature Portfolio, 2018)
Availability of intense hard X-ray pulses allows exploration of multiple ionization effects in heavier elements. Here, the authors measure the complex charge state distributions of xenon and found a reasonable agreement by comparing with the model including the relativistic and resonance effects.